2004
DOI: 10.1001/jama.291.8.974
|View full text |Cite
|
Sign up to set email alerts
|

Different Patterns of Duplicate Publication

Abstract: Context Duplicate publication is publication of an article that overlaps substantially with an article published elsewhere. Patterns of duplication are not well understood. Objective To investigate duplication patterns and propose a decision tree for classification. Data Sources We searched a comprehensive list of systematic reviews (1989 through August 15, 2002) in anesthesia and analgesia that is accessible on the Internet. We selected published full articles of duplicates that had been identified in these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(79 citation statements)
references
References 71 publications
1
74
1
3
Order By: Relevance
“…Six reviewers (5%) analysed the impact of sponsors on the results of the review. B (4,15,26,32),J12,L8 One reviewer claimed that sponsor bias was unlikely, L8 while three were unable to identify any sponsor bias. B(4,15),J12 Finally, two reviews identified sponsor bias (see online supplementary appendix table 3A).…”
Section: Duplicate Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six reviewers (5%) analysed the impact of sponsors on the results of the review. B (4,15,26,32),J12,L8 One reviewer claimed that sponsor bias was unlikely, L8 while three were unable to identify any sponsor bias. B(4,15),J12 Finally, two reviews identified sponsor bias (see online supplementary appendix table 3A).…”
Section: Duplicate Publicationsmentioning
confidence: 99%
“…14 Unreported outcomes may be unearthed by contacting the authors of original articles, and multiple publications based on the same cohort of patients can be identified and excluded from analyses. 15 Authors of systematic reviews (further called: systematic reviewers or reviewers) can also use sensitivity analyses to quantify the impact sponsors' and authors' personal interests have on the conclusions of a review. Finally, it has been suggested that, as part of the process of systematic reviewing, ethical approval of included studies or trials should be checked on in order to identify unethical research.…”
Section: Introduction Rationalementioning
confidence: 99%
“…Academic authors (aka “key opinion leaders”) typically serve as authors, augmenting the credibility of journal articles via their perceived expertise and independence from the sponsor, which enhances the value of the drug brand [1,3]. Most research on duplicative publications has focused on overlapping publications of individual clinical trials [4], whereas pooled analyses have received scant attention [5]. …”
Section: Tablementioning
confidence: 99%
“…112 From the six patterns of duplicate publication (including copy, least publishable unit, meat extender, and disaggregation) that they identify from their analysis of systematic reviews of papers in perioperative medicine, they develop a decision tree for identifying such patterns.…”
Section: Redundancymentioning
confidence: 99%